U.S. Planning for Pandemics and Large-Scale Nuclear War. (5th March 2021) - Eden, Lynn
ABSTRACT: How does the United States develop plans to prevent, prepare for, and/or mitigate disasters? I first discuss planning for the possible: preparedness programs to deal with terror attacks and environmental disasters. I then consider planning for the impossible, or at least, planning for a disaster beyond history: nuclear war. I ask how military planners avoid focusing on the civilizational consequences of the verything they are planning. My answers include two well-known responses: the belief that war plans and capabilities maintain deterrence, and that destroying population is not an objective. I add three additional explanations. Refusing an assignment can be costly for a career. More important, planners focus on solving complex and abstract mathematical problems; this distances them from dwelling on the human consequences. At the same time, planners' jokes demonstrate that they understand the catastrophic consequences were the war plans they develop to be implemented.